Enhancing Tax Compliance in the Energy Sector: PLS-SEM Analysis of Tax Administration Strategies - Iqbal, M.; Sujianto, Sujianto; Erdianto, Erdianto; Ayub, Daeng (International Journal of Energy Economics and Policy, 2023)
The energy sector often constitutes a significant portion of a country's gross domestic product (GDP). It includes industries related to oil, gas, electricity, and renewable energy sources. The size of this sector means that it has a substantial economic impact, contributing to overall economic growth and, in turn, increasing tax revenue. In the context of revenue generation challenges faced by tax authorities, this research explores the pivotal role of tax administration strategies in enhancing tax compliance within the energy sector. Employing a quantitative research methodology with a survey design, this study utilizes structured questionnaires distributed to randomly selected individual taxpayers involved in the energy sector in Indonesia, collecting 178 samples. The research leverages Partial Least Squares Structural Equation Modeling (PLS-SEM) to rigorously test its hypotheses. The findings underscore the critical importance of effective tax administration for augmenting tax compliance within the energy sector and, consequently, increasing tax revenues. The findings empirically prove that tax education, the imposition of law enforcement, and administrative efficiency emerge as key drivers, significantly and positively influencing tax compliance in the energy sector. The findings emphasize the importance of educating individuals and businesses within the energy sector about their tax obligations. Energy companies and workers should be well-informed about tax laws and regulations to encourage voluntary compliance.